Analysis of Tube Expansion Percentage on Microstructure and Hardness of 316L Stainless Steel Tube-to-Tubesheet Connections with GTAW Process - Syaiful Amri, Moh.; Bachtiar, Bachtiar; Miftachul Munir, Moh.; Mukhlis, Mukhlis; Ari, Muhammad; Kurniawan, Ilham (Journal of Mechanical Engineering, Science, and Innovation, 2025)
This study analyzes the effect of varying tube expansion percentages on the mechanical properties, microstructure, and hardness of SA-213 TP316L tubes joined to SA-240 TP316L tubesheets in a shell-and-tube type heat exchanger. The tube expansion process was carried out using a roller expander with three expansion levels: 4%, 8%, and 12%, followed by Gas Tungsten Arc Welding (GTAW) at 150 A. Microstructural observations revealed that all joint zones were dominated by austenite with small amounts of delta ferrite, where increasing expansion percentages induced significant changes in the expand area: slight deformation at 4%, grain elongation at 8%, and pronounced grain distortion at 12%. Macrostructural observations showed perfect fusion between the tube and tubesheet for all variations, with no macro defects such as lack of fusion or porosity. Vickers hardness testing indicated the highest values in the expand area for all variations, with a maximum of 377 Kgf/mm², exceeding the standard limit of 250 Kgf/mm² for stainless steel. The hardness of the base metal was around 180 Kgf/mm², while the weld metal ranged from 220–230 Kgf/mm² due to delta ferrite formation. The increase in hardness in the expand area was attributed to cold working effects, indicating that post-tube expansion heat treatment is necessary to reduce residual stresses and restore the optimal mechanical properties of the material.